PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS POWERPOINT PADA PEMBELAJARAN IPS DI KELAS VIII - Agus Priya Aldiyaksa; Yusawinur Barella; Sri Buwono (Institut Pendidikan Tapanuli Selatan, 2023)
This study aimed to enhance social studies education for eighth graders through the development of an interactive multimedia tool based on PowerPoint. The Research and Development (R&D) method was utilized following the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), although only the first three stages were completed in this study. The Analysis stage included identifying problems and needs as a guide for development. The Design stage involved creating flowcharts, storyboards, collecting necessary materials, and designing assessment instruments. The Development stage encompassed the creation of the interactive multimedia based on PowerPoint. A questionnaire, validated by media, material, and social studies experts, was used to evaluate the product. The experts rated the multimedia at 81.66%, 100%, and 92.94%, respectively, yielding an average rating of 91.53% and a decision of